2021
DOI: 10.1093/ehjci/jeab116
|View full text |Cite
|
Sign up to set email alerts
|

Validation of aortic valve calcium quantification thresholds measured by computed tomography in Asian patients with calcific aortic stenosis

Abstract: Aims Sex-specific thresholds of aortic valve calcification (AVC) have been proposed and validated in Caucasians. Thus, we aimed to validate their accuracy in Asians. Methods and results Patients with calcific aortic stenosis (AS) from seven international centres were included. Exclusion criteria were ≥moderate aortic/mitral regurgitation and bicuspid valve. Optimal AVC and AVC-density sex-specific thresholds for severe AS wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…Recently, Guzzetti et al compared AVC thresholds in Asian and Caucasian populations and concluded that AVC density performed better than AVC in terms of diagnostic accuracy. 23 This is in contrast to the results of the present study; however, Japanese patients were not included in that study. We believe that the adoption of AVC throughout the international guidelines with the same thresholds would be more comprehensive.…”
Section: Discussioncontrasting
confidence: 72%
“…Recently, Guzzetti et al compared AVC thresholds in Asian and Caucasian populations and concluded that AVC density performed better than AVC in terms of diagnostic accuracy. 23 This is in contrast to the results of the present study; however, Japanese patients were not included in that study. We believe that the adoption of AVC throughout the international guidelines with the same thresholds would be more comprehensive.…”
Section: Discussioncontrasting
confidence: 72%
“…Another potentially useful imaging technique for decreasing the frequency of discordant grading is to use AVC on non-contrast multidetector CT, which has emerged as a highly valuable tool for assessing anatomical AS severity and has been incorporated in the latest guidelines 13–15. In a recent paper, we reported that among 312 patients with discordant echocardiographic grading, 158 (50.6%) were deemed to have true severe AS when using sex-specific AVC density thresholds without a significant racial difference in the prevalence of true severe AS 22. In the current study, sex-specific AVC thresholds significantly decreased the frequency of discordant grading in both races and the simultaneous use of both sex-specific AVC thresholds and PR adjustment further decreased the frequency of discordant grading.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Therefore, as interindividual valve size variability is not considered, the current method may lead to an overestimation or underestimation of AS true severity, especially in patients with eccentric, large annuli (ie, patients with bicuspid aortic valve) or very small annuli (smaller patients). [16][17][18] Thus, substantial improvement could potentially be observed in both the diagnosis and management of patients with AS with the implementation of AVCd values in clinical practice as it improves predicting values. 3 The rounded thresholds could be 300 AU/cm 2 in women and 500 AU/cm 2 in men since they provide a similar classification of AS severity for patients in our cohort (data not shown).…”
Section: Additive Value Of Avc Indexationmentioning
confidence: 99%